Archaeological Sources for the History of Palestine: Palestine in the Early Islamic Period: Luxuriant Legacy - Schick, Robert (Near Eastern archaeology, 1998)
Encompassing over four centuries from the Islamic conquest in the 630s CE up to the arrival of the Crusaders in 1099 CE, the Early Islamic period left a prominent and singularly beautiful imprint upon Palestine. While in the past archaeologists were often disinterested in the period, its legacy has recently attracted increased attention. Exciting new data have begun to illuminate a period once known exclusively from historical sources. After beginning with an overview of the history of the era, the author turns to historical geography and the history of exploration. Next, Jerusalem, Christians and Muslims, as well as church building, the destruction of images, and early mosques all receive special attention. A portrait of the nature of Early Islamic settlement ranges from housing to human osteology. An overview of art and architecture concludes the synopsis of a period rich in archaeological remains and historical drama.